2018
DOI: 10.18488/journal.aefr.2018.81.90.102
|View full text |Cite
|
Sign up to set email alerts
|

Accounting Information Comparability and Debt Capital Cost Empirical Evidence from Chinese Listed Companies

Abstract: Article HistoryReceived: 11 July 2017 Revised: 5 December 2017 Accepted: 11 December 2017 Published: 18 December 2017 KeywordsAccounting information comparability Creditor capital cost Accounting information comparability model. JEL Classification: M40, H63The annual samples of 9370 companies from China's Shanghai and Shenzhen A-share market which during the period 2004 to 2013 were used as the object of study for this paper. According to De Franco et al. (2011) comparability models were used to measure accoun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 13 publications
0
6
0
2
Order By: Relevance
“…Specifically, we follow Sun et al (2006) and Lian et al (2011) and use the sum of short-term loans, long-term loans, and noncurrent liabilities due within 1 year to measure the total bank loan. The cost of bank financing is then calculated as interest expense divided by the total bank loan (COST).…”
Section: Other Robustness Tests 16mentioning
confidence: 99%
“…Specifically, we follow Sun et al (2006) and Lian et al (2011) and use the sum of short-term loans, long-term loans, and noncurrent liabilities due within 1 year to measure the total bank loan. The cost of bank financing is then calculated as interest expense divided by the total bank loan (COST).…”
Section: Other Robustness Tests 16mentioning
confidence: 99%
“…According to Sánchez-Ballesta & García-Meca ( 2005), a qualified opinion has a negative impact on financial information users, influencing electoral behaviour, since the economic effects of public policies are reflected in the financial information (Brusca & Montesinos, 2006). Sun et al, (2006) found little impact of qualified audit opinions on the ability to borrow bank loans when local or central governments have a strong influence on companies. Edmonds et al (2020), point out that qualified audit opinions have an impact on municipal market bonds since investors value the information content of an audit report, penalising counties and local governments with qualified/adverse audit opinions…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…Comparability in accounting reduces the cost of information processing and undermines uncertainty about a firm's potential credit risk in both public capital markets [38] and private loans [39]. It helps lower the cost of debt [40] and the cost of equity [41] and assists businesses in accessing trade credit [42]. Thus, comparability capability of financial statements also has an impact on the value created for the stockholders and owners' equity return [43].…”
Section: Financial Statement Comparability and Financial Performancementioning
confidence: 99%